Screening of polymorphisms located in the FGF20 and TMEM175 genes in North Chinese Parkinson’s disease patients - Jing, C.C.; Luo, X.G.; Cui, H.G.; Li, F.R.; Li, P.; Jiang, E.Z.; Ren, Y.; Pang, H. (Genetics and molecular research, 2015)
Genome-wide association studies have reported numerous susceptibility loci for Parkinson's disease (PD). However, there have been few replication studies examining these loci in northern Chinese populations. To evaluate the relationships among 3 polymorphic markers located in the fibroblast growth factor 20 and transmembrane protein 175 genes and the genetic susceptibility to PD in northern Chinese subjects, 2 single nucleotide polymorphisms, and 1 insertion/deletion marker (rs591323 in FGF20; rs6599388 and rs142821586 in transmembrane protein 175 near the G-associated kinase/diacylglycerol kinase theta region) were investigated in 313 PD patients and 318 matched controls. Mismatched multiplex polymerase chain reaction-restriction fragment length polymorphism analysis as well as sequence-specific primer polymerase chain reaction and restriction fragment length polymorphism assays were performed. The genotypic frequency of rs591323 differed significantly between the patient and control groups; however, neither rs6599388 nor rs142821586 was associated with PD. We corrected the Hardy-Weinberg disequilibrium for rs6599388, which was previously reported to be common in 4 Asian descent populations into equilibrium status by simultaneously genotyping rs6599388 and rs142821586. In summary, we found that rs591323 was associated with PD but rs6599388 and rs142821586 were not associated with PD in a northern Chinese population.